Sodium alginate/sinter gel spheres immobilized lysozyme producing strain SJ25 enhanced sludge reduction: Optimization and mechanism. (March 2023) - Yan, Huan; Ali, Amjad; Su, Junfeng; Shi, Jun; Xu, Liang; Huang, Tinglin; Wang, Yuxuan
Graphical abstract: Highlights: Sodium alginate and sinter fixed strain SJ25 (SIPB) promoted sludge reduction. Sodium alginate was used to prolong the action time of lysozyme lysis sludge. Fixed sinter was used to enhance enzyme activity and promote electron transfer. SIP B boosted the viability of microbes and altered their community structure. SIP B strengthened the metabolic capability associated with sludge hydrolysis. Abstract: In order to promote sludge hydrolysis and improve the efficiency of aerobic digestion, the sodium alginate immobilized gel spheres pellet B (SIP B) were prepared using sodium alginate (SA) and sinter as carrier to immobilize lysozyme producing strain SJ25. The optimal conditions for SIP B to promote sludge hydrolysis were 5.6 mg SS -1 dosage and pH of 9.0. Under the optimal condition compared with the control group, the reduction efficiency of suspended solids (SS) in 24 h was increased by 26.89 %, the release of soluble chemical oxygen demand (SCOD) was increased by 517.79 mg L –1, polysaccharide (PS) and protein (PN) concentrations were increased by 186.69 and 368.68 mg L –1, respectively. SIP B enhanced the degradation efficiency of sludge by promote the release of lysozyme, prolonging the action time of the enzyme, enhancing the metabolism and membrane transport of xenobiotics, carbohydrate and amino.